Entanglement between living bacteria and quantized light witnessed by Rabi splitting. (10th October 2018) - Marletto, C; Coles, D M; Farrow, T; Vedral, V
Abstract: We model recent experiments on living sulphur bacteria interacting with quantised light, using the Dicke model. Our analysis shows that the strong coupling between the bacteria and the light, when both are treated quantum-mechanically, indicates that in those experiments there is entanglement between the bacteria (modelled as dipoles) and the quantised light (modelled as a single quantum harmonic oscillator). The existence of lower polariton branch due to the vacuum Rabi splitting, measured in those experiments for a range of different parameters, ensures the negativity of energy (with respect to the lowest energy of separable states), thus acting as an entanglement witness.